2011
DOI: 10.5194/bg-8-459-2011
|View full text |Cite
|
Sign up to set email alerts
|

Deep silicon maxima in the stratified oligotrophic Mediterranean Sea

Abstract: Abstract. The silicon biogeochemical cycle has been studied in the Mediterranean Sea during late summer/early autumn 1999 and summer 2008. The distribution of nutrients, particulate carbon and silicon, fucoxanthin (Fuco), and total chlorophyll-a (TChl-a) were investigated along an eastward gradient of oligotrophy during two cruises (PROSOPE and BOUM) encompassing the entire Mediterranean Sea during the stratified period. At both seasons, surface waters were depleted in nutrients and the nutriclines gradually d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 86 publications
9
67
0
Order By: Relevance
“…which is not altered by uptake due to diatoms in the surface waters because there are insignificant numbers of diatoms (Ignatiades et al, 2009;Psarra et al, 2000). In those locations where diatoms are known to exist, such as at the Mediterranean front (Crombet et al, 2011), it is possible to see decreases in SA due to diatom uptake. The concentration of silica in the 200-500 m layer, which is the intermediate water exported from EMS, was 1-8 µmol Si kg −1 in summer (September-October) and somewhat higher in winter (1-10 µmol Si kg −1 , Fig.…”
Section: Silicic Acid In Porewatersmentioning
confidence: 99%
See 3 more Smart Citations
“…which is not altered by uptake due to diatoms in the surface waters because there are insignificant numbers of diatoms (Ignatiades et al, 2009;Psarra et al, 2000). In those locations where diatoms are known to exist, such as at the Mediterranean front (Crombet et al, 2011), it is possible to see decreases in SA due to diatom uptake. The concentration of silica in the 200-500 m layer, which is the intermediate water exported from EMS, was 1-8 µmol Si kg −1 in summer (September-October) and somewhat higher in winter (1-10 µmol Si kg −1 , Fig.…”
Section: Silicic Acid In Porewatersmentioning
confidence: 99%
“…However there are problems with this simple explanation in the EMS because over large areas there are very low diatom numbers (Ignatiades et al, 2009;Psarra et al, 2000), assumed to be because the nutrient supply to the photic zone is below the threshold required for diatom growth. While Crombet et al (2011) found evidence for what they describe as a "deep glass forest" of diatoms at the bottom of the deep chlorophyll maximum/upper nutricline across the Western Mediterranean Sea (WMS), they only found diatoms in the EMS at locations where there was a locally increased nutrient supply to the photic zone (Straits of Sicily, Mediterranean front and Cyprus eddy). Elsewhere, small non-silicate 4212 M. D. Krom et al: Silica cycling in the ultra-oligotrophic eastern Mediterranean Sea phytoplankton, more efficient in utilising nutrients in limited supply, dominate (Huete-Ortega et al, 2011;Siokou-Frangou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the vertical distribution of DPHs in the water column, there are several records of diatoms actively growing in the subsurface layer (Crombet et al, 2011) or in highly mixed water columns (Backhaus et al, 2003;Smetacek et al, 2012) where cells may be displaced at depth and remain there for long periods of (A) Scheme of the translation products of Pt-DPH in the wild-type and transformation control (Tc), and in two knockout lines (KO1 and 2). Sequences retrieved from KO1 and KO2 lines shown in red, for the different alleles, the mutations in the Pt-DPH locus compared with the wild type, and on the right the nucleotide insertions (+), deletions (2), and/or transversions.…”
Section: Dph Is Present In Diverse Diatom Species and Expressed At DImentioning
confidence: 99%